Proteomics profiling of crassostrea iredalei exposed to toxic alexandrium tamiyavanichii and non-toxic alexandrium leei - Hamdan, Nurul Ashima; Mamat, Siti Noor Hasmiza; Abu Hassan, Muhamad Shafiq; Mohammad Noor, Normawaty; Muhamad Bunnori, Noraslinda (Emirates Research Publishing Limited, Dignified Researchers Publications, 2017)
The black scar oyster, Crassostrea iredalei is part of filter feeder organism and found extremely responsive to alterations in the environment from any natural contamination such as harmful algal blooms (HABs). The commercial demand of oyster is therefore of utmost importance to monitor the presence and effect on related toxins at protein level. Hence, the current study involved the comparison in protein profiles of C. iredalei after exposed to toxic A. tamiyavanichi and non-toxic A. leei for 24-hour. This aimed is achievable using two-dimensional gel electrophoresis (2-DE) that can identify the differential abundances of proteins spots for oyster’s protein profiling. There were 12 spots detected in a pH range of 3-10 that can be predicted via cross-referring of the protein molecular weight and isoelectric points, pI in Expasy databases. These predicted proteins were involved in biological activities such as energy metabolism, cell regulation and stress response. Besides that, there were two proteins spots that have been expressed in the toxic sample and further identified using LCMS analysis. Both proteins; arginine kinase and transgelin, were highly expressed in intoxicated oyster due to the oxidative stress induced by the toxic microenvironment. The presence of A. tamiyavanichi caused toxin accumulation in oysters and might induce the disorder of energy metabolism. The regulation mechanism thus explains on the oyster stability during HAB outbreak.